122k views
3 votes
5(×-4)+3×-9×=6-(2×+5)+8×

User Atl
by
5.6k points

2 Answers

4 votes
5x-20+3x-9x=6-2x-5+x

-x-20=1+6x

-x-6x=1+20

-7x=21

X=-3
User Sonu Kumar
by
6.2k points
5 votes
Assuming the × signs are actually x's-

5(x - 4) + 3x - 9x = 6 - (2x + 5) + 8x

Apply the distributive property.

5(x - 4) + 3x - 9x = 6 - (2x + 5) + 8x
5x - 20 + 3x - 9x = 6 - 2x + 5 + 8x

Combine like terms.

5x - 20 + 3x - 9x = 6 - 2x + 5 + 8x
-1x - 20 = 1 + 6x

Add 20 to both sides.

-1x - 20 = 1 + 6x
-1x = 21 + 6x

Subtract 6x from both sides.

-1x = 21 + 6x
-7x = 21

Divide both sides by -7.

-7x = 21
x = -3

Answer:
x = -3

I hope this answers your question!
User Xiaoqi Chu
by
6.0k points